'Do As We Say, Not as We Do:' a cross-sectional survey of injuries in injury prevention professionals. Issue 3 (23rd September 2013) - Ezzat, Allison; Brussoni, Mariana; Schneeberg, Amy; Jones, Sarah J
Abstract : Background: As the leading cause of death and among the top causes of hospitalisation in Canadians aged 1–44 years, injury is a major public health concern. Little is known about whether knowledge, training and understanding of the underlying causes and mechanisms of injury would help with one's own prevention efforts. Based on the Theory of Planned Behaviour, we hypothesised that injury prevention professionals would experience fewer injuries than the general population. Methods: An online cross-sectional survey was distributed to Canadian injury prevention practitioners, researchers and policy makers to collect information on medically attended injuries. Relative risk of injury in the past 12 months was calculated by comparing the survey data with injury incidence reported by a comparable subgroup of adults from the (Canadian Community Health Survey (CCHS)) from 2009 to 2010. Results: We had 408 injury prevention professionals complete the survey: 344 (84.5%) women and 63 (15.5%) men. In the previous 12 months, 86 individuals reported experiencing at least one medically attended injury (21 235 people per 100 000 people); with sports being the most common mechanism (41, 33.6%). Fully 84.8% individuals from our sample believed that working in the field had made them more careful. After accounting for age distribution, education level and employment status, injury prevention professionals were 1.69 (95% CI 1.41 to 2.03) times more likely to be injured in the past year. Interpretation: Despite their convictions of increasing their own safety behaviour and that of others, injury prevention professionals' knowledge and training did not help them prevent their own injuries.